Critical Thinking Ability of Student with Reflective Cognitive Style in Solving Algebraic Numeracy Problems - Aliya, Afifa; Masriyah, Masriyah; Sari, Yurizka Melia (MATHEdunesa, 2025)
Critical thinking is needed in problem solving. To solve problems, students will use a variety of strategies. Critical thinking ability play a role in determining the strategy used, which is also influenced by students' cognitive styles. In this research, the cognitive style discussed is reflective cognitive style. This research is a qualitative with a case study approach. This research aims to describe the critical thinking ability of students in solving algebraic numeracy problems based on reflective cognitive style. This research was conducted in Class VIII Junior High School students. The research subjects were selected through MFFT (Matching Familiar Figure Test) and Mathematical Ability Test. Data analysis techniques include data reduction, data display, and conclusions. The selected research subjects from reflective took the critical thinking ability test and interviews. The results of the critical thinking test and interviews were analyzed to describe the critical thinking in solving algebraic numeracy problems. The results showed that reflective cognitive style student fulfill each criteria of critical thinking ability FRISCO (Focus, Reason, Inference, Situation, Clarity and Overview). The reflective student is able to carry out the focus and reason criteria of critical thinking ability by identifying the main points of the problem and providing reasons for the relationship between what is known and asked correctly and completely. Reflective student is able to carry out the inference and situation criteria by deciding on the right strategy and solving the problems given correctly and systematically. Reflective student can also able to carry out the clarity and overview criteria of critical thinking ability by drawing conclusions and re-examining the solution of the problems given. So, reflective cognitive style student is categorized as very critical. It is suggested that teachers provide more practice questions and provide further discussion with limited working time.